LIFELONG LEARNING: NEW PARADIGMS AND SUSTAINABLE PERSPECTIVES - Rasulova, Durdona Bakhronovna (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2022)
In this article, the author deals with the importance of the concept of "lifelong learning", highlighting life situations and the culture of education and employment, creating a comparative and causal analysis of the theory of lifelong learning. The author also gives possible ways of developing this direction and the results we will encounter in the future.